Correspondence in relation to the case report “Capnography as an aid in localizing the phrenic nerve in brachial plexus surgery. Technical note.” published in May issue of Journal of Brachial Plexus and Peripheral Nerve Injury - Bhakta, Pradipta (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
Comment on ’Capnography as an aid in localizing the phrenic nerve in brachial plexus surgery. Technical note’ Bhagat H, Agarwal A, Sharma MSJournal of Brachial Plexus and Peripheral Nerve Injury 2008, 3:14 (22 May 2008)